Atom Probe Study of 1-Octadecanethiol Self-Assembled Monolayers on Platinum (111) and (200) Surfaces. (August 2022) - Solodenko, Helena; Stender, Patrick; Schmitz, Guido
Abstract: Abstract : Atom probe tomography measurements of self-assembled monolayers of 1-octadecanethiol on platinum tips were performed and their fragmentation behavior under the influence of different laser powers was investigated. The carbon backbone evaporates in the form of small hydrocarbon fragments consisting of one to four carbon atoms, while sulfur evaporates exclusively as single ions. The carbon molecules evaporate at very low fields of 5.9 V/nm, while S requires a considerably higher evaporation field of 23.4 V/nm. With increasing laser power, a weak, but noticeable trend toward larger fragment sizes is observed. No hydrocarbon fragments containing S are detected, indicating that a strong S–Pt bond has formed. The observed surface coverage of S fits well with literature values and is higher for (111)-oriented samples than for (200).